Metabolic syndrome markers and risk of hyperglycemia in pregnancy: a cross-sectional cohort study - Vernini, Joice M. [UNESP]; Nicolosi, Bianca F. [UNESP]; Arantes, Mariana A. [UNESP]; Costa, Roberto A. [UNESP]; Magalhães, Claudia G. [UNESP]; Corrente, José E. [UNESP]; Lima, Silvana A. M. [UNESP]; Rudge, Marilza V. [UNESP]; Calderon, Iracema M. [UNESP] (Springer Nature, 2020)
The aim was to assess the role of Metabolic Syndrome (MetS) diagnostic markers, recommended by three different guidelines, in the prediction of hyperglycemia in pregnancy. This cross-sectional cohort study included 506 non-diabetic women, with a singleton pregnancy, who underwent a diagnostic test for hyperglycemia at 24–28 weeks. Clinical, anthropometric, and laboratory data were obtained. The relationship between MetS markers and the risk of hyperglycemia was evaluated by backward stepwise logistic regression analysis (OR, 95% CI). The limit of statistical significance was 95% (p < 0.05). Triglycerides (TG) ≥ 150 mg/dL, blood pressure (BP) ≥ 130/85 mmHg, fasting glucose (FG) ≥ 100 mg/dL, and waist circumference (WC) > 88 cm were identified as independent risk factors for hyperglycemia in pregnancy. These results might help the selective screening of hyperglycemia in pregnancy.